2006
DOI: 10.1002/anie.200602203
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tellurido‐Bridged IrPt2, IrPd2, and IrPtPd Clusters by Inserting Zero‐Valent Pt and Pd Centers into TeC Bonds

Abstract: Soluble transition-metal sulfido clusters have been investigated extensively because of their relevance to biological and industrial catalysts. In contrast, the chemistry of the analogues of tellurium, the heavier congener of sulfur, has been less-well developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…In the previous paper [3], we have reported the formation of the triangular clusters with two capping tellurido ligands [Cp * Ir-(CO)(l 3 Now we have found that when 1 is allowed to react with an equimolar amount of Pd(II) complex [PdCl 2 (cod)] (cod = 1,5-cyclooctadiene) at room temperature, the tellurolato-bridged heterobimetallic complex [Cp * Ir(CO)(l-TeTol) 2 PdCl 2 ] (2) is obtained in moderate yield (Eq. (1)).…”
Section: Reactions Of 1 With Pd(ii) and Pt(ii) Complexesmentioning
confidence: 96%
See 2 more Smart Citations
“…In the previous paper [3], we have reported the formation of the triangular clusters with two capping tellurido ligands [Cp * Ir-(CO)(l 3 Now we have found that when 1 is allowed to react with an equimolar amount of Pd(II) complex [PdCl 2 (cod)] (cod = 1,5-cyclooctadiene) at room temperature, the tellurolato-bridged heterobimetallic complex [Cp * Ir(CO)(l-TeTol) 2 PdCl 2 ] (2) is obtained in moderate yield (Eq. (1)).…”
Section: Reactions Of 1 With Pd(ii) and Pt(ii) Complexesmentioning
confidence: 96%
“…Solvents were dried by common methods and distilled under N 2 before use. Complexes 1 [3], [MCl 2 (cod)] (M = Pd [8], Pt [9]), [(Cp * MCl) 2 (l-Cl) 2 ] (M = Ir, Rh) [10], [(Cp * Ru) 4 (l 3 -Cl) 4 ] [11], and [RuH(cod)(MeCN) 3 ][BPh 4 ] [12] were prepared according to the literature methods, while KPF 6 was obtained commercially and used as received.…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate restraints and / or constraints were used to keep the bond distances, angles, and thermal ellipsoids meaningful. Usually in tellurido‐bridged cluster complexes, the Pd−Te bond distances observed in the range of 2.60‐2.70 Å . The shortest metal…metal distances found with Te1…Te3 (3.32 Å) and Pd3…Pd4 (3.21 Å) separation.…”
Section: Resultsmentioning
confidence: 97%
“…{PtTol(PPh 3 )}](Fig. 16), which was formed by the facile inversion of the Pd(0) center in to a Te-Tol bond in the complex [CpIr(CO)(m-Te)(m-TeTol){PtTol(PPh 3 )}] 126,157. Similarly, [Pt(TeR) 2 (dppe)] (R ¼ Ph, Fc) upon reaction with a rhenium carbonyl cluster yielded heterometallic tellurolato bridged complexes [(dppe)Pt(m-TeR) 2 ReCl(CO) 3 ] (R ¼ Ph, Fc) 158,159.…”
mentioning
confidence: 99%